EFL teachers’ role in English: Letting the silent majority voice their words - Babaii Esmat; Atai Mahmood Reza; Parsazadeh Abbas (ExELL (Explorations in English Language and Linguistics))
With the advent of the global perspective on English, the live issues of the ownership and culture of English (Akbari, 2008; Seidlhofer, 2005) have begun to shake up numerous conventional notions of the field. In the wake of this landmark shift, this study attempts to probe EFL teachers’ cultural attitude toward prospective English words. To this end, identifying twelve highly Persian culture-specific words, the researchers devised an attitude questionnaire, which was administered to 351 EFL teachers to examine their right of cultural encoding (Kirkpatrick, 2014) as English users. The study concludes with granting a legitimate norm-overriding role to EFL teachers in order to gate-keep their required concepts in English.